Demand-driven training and job turnover: The effects of Brazil's Pronate-MDIC at firm and worker level - Rodrigo E. Quintana; Túlio Cravo (Inter-American Development Bank (IDB), 2019)
This paper explores for the first time the impact of a demand-driven training program on labor turnover at both firm and worker level. Launched in 2014 by the Ministry of Development, Industry and Trade (MDIC in Portuguese), Pronatec-MDIC allows firms to demand courses which some of their workers apply to. Difference-in-difference estimates find that workers who enroll in the courses demanded by their employers increase their job tenure by 8.89 months compared to non-enrolled nominees. However, those who complete the training stay in the job 3.36 months less, on average, than those who do not. At firm level, results show that having a course approved is associated with higher turnover in the short run when considering subgroups of workers who participate in Pronatec-MDIC. The effect dissipates in the third year, suggesting that it takes time for firms to adjust their labor stock after course demand but stabilize afterwards.
Keywords: J24; J63; P46; 330; Education and Training; Turnover; Human Capital